2022
DOI: 10.3389/fmed.2022.918657
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diagnostic gene biomarkers and immune infiltration in patients with diabetic kidney disease using machine learning strategies and bioinformatic analysis

Abstract: ObjectiveDiabetic kidney disease (DKD) is the leading cause of chronic kidney disease and end-stage renal disease worldwide. Early diagnosis is critical to prevent its progression. The aim of this study was to identify potential diagnostic biomarkers for DKD, illustrate the biological processes related to the biomarkers and investigate the relationship between them and immune cell infiltration.Materials and methodsGene expression profiles (GSE30528, GSE96804, and GSE99339) for samples obtained from DKD and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…PRKAR2B was also discovered to enhance prostate cancer metastasis by activating the Wnt/β-catenin signaling pathway. 26 Some studies suggested that PRKAR2B can serve as a potential biological marker for diabetic kidney disease 27 , 28 , 29 , 30 and squamous cell carcinoma. 31 PRKAR2B has been found to be related to various other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…PRKAR2B was also discovered to enhance prostate cancer metastasis by activating the Wnt/β-catenin signaling pathway. 26 Some studies suggested that PRKAR2B can serve as a potential biological marker for diabetic kidney disease 27 , 28 , 29 , 30 and squamous cell carcinoma. 31 PRKAR2B has been found to be related to various other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There are limitations to our study. First, CKD is an umbrella term with significant heterogeneity, and we were not able to analyze specific types of CKD; Second, we focus on the pathogenesis and diagnostic markers of CKD in the context of NAFLD, and it is important to note that CKD has the opposite effect on NAFLD, which is beyond the scope of our discussion; Third, our findings were required to validate in vivo and in vitro to better guide clinical practice, although the decreased expression of DUSPI and ZFP36 in CKD has been confirmed by related studies (36,53).…”
Section: A B D Cmentioning
confidence: 94%
“…Juan Jin et al 73 identified biomarkers, including CTLA-4, CXCR3, CCR4, CD39, PD-1, and HLA-DR, via mass cytometry (CyTOF) analysis, which are associated with significantly altered monocyte, T cell, and B cell subpopulations in early-stage DKD; however, further validation in other cohorts is necessary. Shaojie Fu et al 121 used three different algorithms, including least absolute shrinkage and selection operator (LASSO), support vector machine-recursive feature elimination (SVM-RFE), and random forest (RF), to identify DUSP1 and PRKAR2B as possible biomarkers. Further, immunohistochemical staining indicated that DUSP1 and PRKAR2B expression levels were significantly decreased in patients with DKD.…”
Section: Bioinformatics Analysis Of Immune Cells In Dkdmentioning
confidence: 99%